2021
DOI: 10.3928/01913913-20210122-02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Treatment of Retinopathy of Prematurity at a Tertiary Care Hospital in Saudi Arabia: A Retrospective Study

Abstract: Purpose: To estimate the prevalence of retinopathy of prematurity (ROP) among high-risk neonates and to illuminate the benefits of early treatment in type 2 ROP (zone II, stage 3 without plus) and ROP milder than type 1 with pre-plus disease (zone III, stage 3). Methods: This retrospective cross-sectional study was conducted among 307 high-risk neonates (614 eyes) with a gestational age of 32 weeks or younger at birth and a birth weight of 1,500 g or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the present study, earlier treatment for ROP was adapted in our center, based on a previous study done on our population that highlighted the benefit of early treatment of type 2 ROP and ROP milder than type 1, in which they had significantly decreased rates of progression to more advanced stages and had resulted in good clinical outcomes. [ 23 ] In our study, the hyperopic trend that was noted in our patients could be related to the early quantification of spherical equivalence in terms of follow-up visits. In subsequent years, our patients may develop more levels of myopia attributed to the normal expected emmetropization that should ensue throughout the years.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the present study, earlier treatment for ROP was adapted in our center, based on a previous study done on our population that highlighted the benefit of early treatment of type 2 ROP and ROP milder than type 1, in which they had significantly decreased rates of progression to more advanced stages and had resulted in good clinical outcomes. [ 23 ] In our study, the hyperopic trend that was noted in our patients could be related to the early quantification of spherical equivalence in terms of follow-up visits. In subsequent years, our patients may develop more levels of myopia attributed to the normal expected emmetropization that should ensue throughout the years.…”
Section: Discussionmentioning
confidence: 56%
“…Early treatment has been adopted in our center based on a previous study done on our population which reported the benefit of early treatment of type 2 ROP and ROP milder than type 1. [ 23 ] The ETROP study findings provided definite guidelines for the treatment of ROP; however, despite the well-defined criteria for treatment, experts in ROP also highlighted the clinical implications and recommended treatment for patients with less than type 1 ROP in previous multicenter studies. [ 24 25 ] ROP experts in those studies also highlighted the importance of clinical judgment in individual cases which are not covered by treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%